The Corrosion Resistance and Mechanism of AT13/Fe-Based Amorphous Composite Coatings - Zhenhua Chu; Shikun Teng; Yuyun Zhou; Xingwei Zheng; Jingxiang Xu; Fang Wang; Baosen Zhang (Micromachines, 2021)
Due to high strength, high wear resistance and high corrosion resistance, the amorphous metallic glasses were investigated widely. In the present study, the corrosion resistance of amorphous coating and composite coatings with various proportions of AT13 (Al2O3–13 wt.% TiO2) ceramic as additions in 3.5 wt.% NaCl solution were studied. The corrosion resistance was improved obviously as the addition of AT13, and when the content of AT13 was 15 wt.%, the composite coating had the lowest corrosion current density (1.75 × 10−6 A cm−2) and the highest corrosion potential (−411 mV), which was 5.14 × 10−5 A cm−2 and −580 mV for Fe-based metallic glassy coating, respectively. The corrosion mechanism was proposed according to the long-time immersion corrosion test.